Foucault and classical antiquity : power, ethics and knowledge - Detel, Wolfgang (Modern European philosophy., 2005)
This 2005 book is a critical examination of Michel Foucault's relation to ancient Greek thought, in particular his famous analysis of Greek history of sexuality. Wolfgang Detel offers an understanding of Foucault's theories of power and knowledge based on modern analytical theories of science and concepts of power. He offers a complex reading of the texts which Foucault discusses, covering topics such as Aristotle's ethics and theory of sex, Hippocratic dietetics, the earliest treatises on economics, and Plato's theory of love. The result is a philosophically rich and probing critique of Foucault's later writings, and a persuasive account of the relation between ethics, power and knowledge in classical antiquity. His book will have a wide appeal to readers interested in Foucault and in Greek thought and culture.